A method for calculating radial time-varying stiffness of flexible cylindrical roller bearings with localized defects. (October 2021) - Xu, Hongyang; He, Duo; Ma, Hui; Yu, Kun; Zhao, Xiang; Yang, Yang
Highlights: A calculation method of radial time-varying stiffness of cylindrical roller bearings is proposed. The proposed method considers the flexibility of bearing parts. The proposed method takes into account the localized defects of bearing parts. The proposed method is more accurate than the traditional analytical method. The proposed method is more efficient than the finite element method. Abstract: In this paper, the flexibility of bearing parts and localized defects are considered, and a method for calculating the radial time-varying stiffness of flexible cylindrical roller bearings (CRBs) with localized defects is proposed. The proposed method uses the finite element (FE) method to calculate the global flexibility of bearing parts and adopts the analytical contact theory to calculate the localized contact flexibility of bearing parts. Furthermore, based on the displacement excitation assumption, localized defect models of the outer race, inner race, and roller are established. The proposed method is verified by comparing with the methods in the references and the finite element method. The effect of different angles of defect width on time-varying stiffness is discussed. The results show that as the angle of defect width increases, the width of the stiffness saltation also gradually increases. Besides, the calculation accuracy of the proposed method is higher than that of the classical analytical method, and the computational efficiency is greatly improved compared with the finite element method. This study can provide a theoretical basis for defect diagnosis of CRBs.